OPPORTUNITIES OF USING CARTOGRAPHIC METHODS IN TEACHING BIOLOGY IN HIGHER EDUCATION. - Jololdinov Asror Toshtemirovich; Samijonova Gulzira Esonboy qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The integration of interdisciplinary approaches in higher education is pivotal for enhancing the quality of biological sciences instruction. This article explores the significant yet underutilized opportunities presented by cartographic methods—the science and technology of making and using maps—in teaching biology at the university level. The modern biological sciences, encompassing ecology, genetics, anatomy, and biogeography, are inherently spatial disciplines. Cartographic techniques, particularly Geographic Information Systems (GIS), thematic mapping, and geovisualization, provide powerful tools to visualize, analyze, and interpret complex biological data. This paper analyzes the didactic potential of these methods for improving spatial thinking, fostering interdisciplinary understanding, and engaging students in active, research-based learning. The analysis concludes that the strategic implementation of cartographic tools can transform biology education from a static, fact-based discipline into a dynamic, analytical, and problem-solving oriented field, thereby preparing students for the challenges of modern scientific research and environmental management.